2011
DOI: 10.1038/nature10172
|View full text |Cite
|
Sign up to set email alerts
|

Genomic island variability facilitates Prochlorococcus–virus coexistence

Abstract: Prochlorococcus cyanobacteria are extremely abundant in the oceans, as are the viruses that infect them. How hosts and viruses coexist in nature remains unclear, although the presence of both susceptible and resistant cells may allow this coexistence. Combined whole-genome sequencing and PCR screening technology now enables us to investigate the effect of resistance on genome evolution and the genomic mechanisms behind the long-term coexistence of Prochlorococcus and their viruses. Here we present a genome ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
342
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(360 citation statements)
references
References 33 publications
16
342
2
Order By: Relevance
“…Whole-genome phylogeny analysis was performed as previously described (Avrani et al, 2011) using custom python scripts. The predicted protein sequences of each genome were compared with those of the other genomes using BLASTP (Altschul et al, 1997); reciprocal best blast hits of ⩾ 50% identity, aligned over ⩾ 70% of the length of both Non-symbiotic Bradyrhizobia dominate forest soils D VanInsberghe et al query and subject sequences were defined as orthologous genes.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Whole-genome phylogeny analysis was performed as previously described (Avrani et al, 2011) using custom python scripts. The predicted protein sequences of each genome were compared with those of the other genomes using BLASTP (Altschul et al, 1997); reciprocal best blast hits of ⩾ 50% identity, aligned over ⩾ 70% of the length of both Non-symbiotic Bradyrhizobia dominate forest soils D VanInsberghe et al query and subject sequences were defined as orthologous genes.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…are under a constant threat of phage infection (Mann 2003, Avrani et al, 2011. Cyanophages infecting fi lamentous heterocystous cyanobacteria seem to be less frequent (Hu et al, 1981).…”
Section: Crispr Phage Immunity Systemmentioning
confidence: 99%
“…Thus, like other phytoplankton, the life and death of Prochlorococcus are intimately coupled with that of co-occurring microbes. Although significant advances have been made in understanding 'top down' control of Prochlorococcus populations by phage and grazers (for example, Worden and Binder, 2003;Avrani et al, 2011;Pasulka et al, 2015), as well as 'bottom up' control by nutrients, temperature and light (for example, Bouman et al, 2006;Johnson et al, 2006;Saito et al, 2014), studying how co-occurring heterotrophic microbes affect Prochlorococcus is still in its infancy. Several recent studies have shown that co-occurring heterotrophic bacteria can both enhance and inhibit the growth of Prochlorococcus in laboratory co-cultures (Morris et al, 2008;Sher et al, 2011).…”
Section: Introductionmentioning
confidence: 99%